2013
DOI: 10.1111/ceo.12140
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, controlled trial of conjunctival autografting combined with subconjunctival bevacizumab for primary pterygium treatment: 1‐year follow‐up

Abstract: A single 2.5 mg/mL subconjunctival bevacizumab injection in conjunction with primary pterygium surgery accomplishing a conjunctival autograft procedure is safe and well tolerated, and is capable of preventing pterygium recurrences when compared with a control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 35 publications
0
21
0
1
Order By: Relevance
“…Nava-Castañeda et al have studied the efficacy of 2.5 mg/0.1 ml of conjunctival autograft and two subconjunctival bevacizumab (the first one immediately after surgery and the second one after 15 days) in reducing recurrence of the disease, with satisfactory results after a 1-year follow-up [29]. Another study performed by Ozsutcu et al evaluated the use of an intraoperative bevacizumab injection, with the same dosage, associated with pterygium excision with rotational conjunctival flap followed by another injection after 1 week, reporting significantly less recurrence than rotational flap alone [30].…”
Section: Discussionmentioning
confidence: 99%
“…Nava-Castañeda et al have studied the efficacy of 2.5 mg/0.1 ml of conjunctival autograft and two subconjunctival bevacizumab (the first one immediately after surgery and the second one after 15 days) in reducing recurrence of the disease, with satisfactory results after a 1-year follow-up [29]. Another study performed by Ozsutcu et al evaluated the use of an intraoperative bevacizumab injection, with the same dosage, associated with pterygium excision with rotational conjunctival flap followed by another injection after 1 week, reporting significantly less recurrence than rotational flap alone [30].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of recurrence in the bevacizumab group was half that of the BSS group in their study, but this failed to reach statistically significant difference. Another study by Nava-Castaneda et al 23 reported no recurrence in the two groups that had subconjunctival bevacizumab injections after a 1 year follow-up period with recurrence only in the third group which had no injection given. This difference was statistically significant and they concluded that a single 2.5 mg/ml subconjunctival bevacizumab injection in conjunction with primary pterygium surgery accomplishing a conjunctival autograft procedure was safe, well-tolerated, and capable of preventing pterygium recurrences.…”
Section: Discussionmentioning
confidence: 93%
“…[19][20][21][22] A randomized clinical trial reported the use of subconjunctival bevacizumab injection in conjunction with primary surgery and conjunctival autograft to be safe, well-tolerated, and capable of preventing recurrence when compared with the control. 23 Another randomized trial showed no statistically significant difference between the bevacizumab group and control, although recurrence rate was halved in the former. 24 The purpose of this study is to compare 5-FU with conjunctival autograft and bevacizumab (avastin) used along with autograft in the surgical treatment of pterygium.…”
Section: Introductionmentioning
confidence: 98%
“…(2) Individual differences in the sensitivity to VEGF and its inhibitors may exist, which could account for the difference in the outcomes of treatment using antiangiogenic agents. [31][32][33][35][36][37] (3) Recurrence of pterygium may be induced by a multifactorial process with many confounding factors. 19 Thus, inhibition of the VEGF pathway would not be enough for the prevention of recurrence.…”
Section: Discussionmentioning
confidence: 99%